The Correlation Between the Type of Fluid Administration and the Incidence of Hypotension in Patients Undergoing Spinal Anesthesia at RS Wijayakusuma Purwokerto - Taufiqurrahman, Sauqi; Cing, Marta Tania Gabriel Ching (Proceedings Series on Health & Medical Sciences, 2025)
Background: Spinal anesthesia is a type of regional anesthesia that involves injecting a local anesthetic into the subarachnoid area. The effect of sympathetic blockade in spinal anesthesia can cause dilation of blood vessels, suppress systemic vascular resistance and result in hypotension [1]. The effects of hypotension are pulmonary aspiration, cardiac arrest, respiratory depression, and loss of consciousness. A sudden drop in blood pressure can also cause a heart attack, a complication of spinal anesthesia. Method: A quantitative approach using a correlational observational design with research variables, namely the administration of fluid types with the incidence of hypotension in patients undergoing spinal anesthesia. The research was conducted in the IBS room at Wijayakusuma Hospital, Purwokerto, with samples was calculated obtained 53 respondents who were selected using a purposive sampling technique. The relationship between the two variables tested was carried out using the non-parametric chi square statistical test with the Fisher exact test Results: Among the respondents, the type of fluid administered was crystalloids in 98.1% of cases, with 70.2% of respondents not experiencing hypotension. The chi-square test yielded a p-value of 1.000, indicating no significant correlation between the type of fluid administered and the incidence of hypotension in patients undergoing spinal anesthesia. Conclusion: There is no significant correlation between the administration of crystalloid or colloid fluids and the incidence of hypotension in patients undergoing spinal anesthesia at RST Wijayakusuma Purwokerto.